PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAN 1 V KOTO KAMPUNG DALAM - Yusticha Oktavia Murni (Departemen Matematika, 2021)
Understanding of mathematical concepts has a very important roles in mathematics. Based on the results of observations in class XI MIPA SMAN 1 V Koto Kampung Dalam, it can be seen the students' undestanding of mathematical concept is still low. One of the causes is the use of learning models that do not actively involve students in the learning process. Therefore, a research was conducted by applying a think talk write (TTW) cooperative learning model with the aim of increasing students' understanding of mathematical concepts. Learning is carried out online as a results of the implementation of restrictions on community activities to prevent the transmission of Covid-19 in the school environment. For this reason, learning is carried out online by using WhatsApp and Google Meet. This type of research is a quasy-Experiment with Static Group Design. The population is all students of class XI MIPA SMAN 1 V Koto Kampung Dalam with two classes being sampled through a simple random sampling technique, namely class XI IPA 4 as the experimental class and XI IPA 3 as the Control class. The instrument used in this study was a mathematical concept understanding test given at the end of the lesson. from the result of data’ analysist with a significant level of α, obtain p-value = 0.000. Thus, it can be concluded that the understanding of mathematical concept of students who study using the TTW model is better than students who learn using the directs learning model. Keywords– understandings of mathematicals concepts, Think Talk Write, quasi-experimental